Plano municipal de saneamento básico no município de Aracaju e o novo marco legal - Almeida, Iasmine Louise de (2022)
Basic sanitation is one of the main elements in the infrastructure of a place, in addition to preventing waterborne diseases and epidemiological contamination. Basic Sanitation Municipal Plans are documents made up of stages that consider a deep understanding of sanitation issues and the municipal territory regarding existing social interventions and the future scenario. In 2020, the new legal framework for basic sanitation was instituted, Law nº 14.026/2020, which determined the mandatory elaboration of the municipal basic sanitation plan (PMSB) and established the National Water Agency, as also responsible for regulating norms referring to basic sanitation in Brazil. The municipality of Aracaju, through Law number 4,973 of December 11, 2017, instituted its Basic Sanitation Plan. As it is a plan prepared before the new legal framework, the present work aimed to analyze whether the PMSB of Aracaju met the goals established for the short term (4 years) as well as whether they are in accordance with the new guidelines established in the legislation now in effect. It is concluded that the information on the actions carried out in the municipality of Aracaju in the last four years regarding the four aspects of sanitation differed from the established goals, mainly due to a pandemic period of 2 years that made the allocation of resources for these purposes unfeasible. As for the new legal framework for sanitation, the regionalization of some services related to sanitation is not indicated for the municipality of Aracaju, mainly because it is a coastal city.